Higher Hospitalization Rate for Lower Airway Infection in Transfusion-Naïve Thalassemia Children - Tsai, Ti-An; Tsai, Chang-Ku; Yang, Yao-Hsu; Lee, Zon-Min; Sheen, Jiunn-Ming; Lee, Yi-Chen; Tsai, Chih-Min; Chen, Chih-Cheng; Chang, Chih-Hao; Niu, Chen-Kuang; Yu, Hong-Ren (Frontiers in Pediatrics, 2020)
Few studies have addressed the risk of infection in transfusion-naïve thalassemia patients. We aimed to investigate whether transfusion-naïve thalassemia population has higher hospitalization rates for lower airway infection-related diseases than non-thalassemia population in children. A nationwide population-based retrospective cohort study was conducted using detailed medical records of the Taiwan National Health Insurance Research Database. Transfusion-naïve thalassemia patients were compared with a matched cohort at a ratio of 1:4. Data of the selected patients were adjusted for age, sex, and related comorbidities. We recorded the frequency of admissions or outpatient clinic visits for patients with a diagnosis of pneumonia or acute bronchitis/bronchiolitis. Based on our results, the hospitalization rates and incidence rate ratios of bronchitis/bronchiolitis and pneumonia for transfusion-naïve thalassemia children were all higher than those for non-thalassemia controls. Therefore, we conclude that transfusion-naïve thalassemia children are more likely to experience lower airway infections and have a higher probability of hospitalization for these conditions.